2022
DOI: 10.3892/ol.2022.13244
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for atrial fibrillation in active cancer (Review)

Abstract: Atrial fibrillation (AF) may often pre-exist in patients with newly diagnosed cancer or occur with increased frequency shortly after cancer diagnosis. Patients with active cancer and AF have a particularly high risk of thromboembolic complications, as both conditions carry a risk of thrombosis. Thromboembolic risk is determined by several factors, including advanced age, sex (females), cancer histology (adenocarcinomas), location (e.g., pancreas, stomach), advanced stage, anticancer regimens (e.g., platinum co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Regarding the assessment of the bleeding risk, the HAS-BLED was quite accurate [47], although the HEMORR2HAGES score also includes a history of malignancy and thrombocytopenia in the risk assessment (Table 3) [48]. The latter is an important finding, as it has been shown that platelets < 100,000 × 10 9 /L increase the risk of bleeding for cancer patients taking anticoagulants and tumors together with cancer treatments may cause thrombocytopenia [33,49]. Farmakis et al proposed an alternative approach for risk stratification that includes the following acronyms: T (thrombotic risk), B (bleeding risk), I (drug interactions), and P (patient access and preferences) [50].…”
Section: Anticoagulant Treatmentmentioning
confidence: 99%
“…Regarding the assessment of the bleeding risk, the HAS-BLED was quite accurate [47], although the HEMORR2HAGES score also includes a history of malignancy and thrombocytopenia in the risk assessment (Table 3) [48]. The latter is an important finding, as it has been shown that platelets < 100,000 × 10 9 /L increase the risk of bleeding for cancer patients taking anticoagulants and tumors together with cancer treatments may cause thrombocytopenia [33,49]. Farmakis et al proposed an alternative approach for risk stratification that includes the following acronyms: T (thrombotic risk), B (bleeding risk), I (drug interactions), and P (patient access and preferences) [50].…”
Section: Anticoagulant Treatmentmentioning
confidence: 99%
“…For bleeding risk assessment, the HAS-BLED score may be considered [ 62 ]. A proposed approach to anticoagulant therapy in cancer is based on the acronym T (thrombotic risk), B (bleeding risk), I (drug interactions), P (access and patient preferences) [ 71 ].…”
Section: Indications For Anticoagulant Therapy In Cancer Patientsmentioning
confidence: 99%
“…Active malignancy amplifies the thromboembolic risk in patients with AF due to its hypercoagulable state, creating a challenge in anticoagulation [15]. Thrombocytopenia due to chemotherapy-induced bone marrow suppression can further complicate this situation.…”
Section: Challenges Associated With the Management Of Atrial Fibrilla...mentioning
confidence: 99%